Sort by

- Relevance
- |Time

**k**^0.5 = 6 square the whole equation (**k**^0.5 = 6)^2**k**= 6^2**k**= 36 RainMaker nifty-rainmaker.blogspot.com/5 Answers · Science & Mathematics · 11/05/2010

Let

**K**be a convex subset of R^p and let x,y be in the closure of**K**. Then there exist sequences (x_n), (y_n) of points in**K**such that lim x_n = x and lim y_n = y. The line segment between x_n and y_n...2 Answers · Science & Mathematics · 20/01/2012

(

**k**+ 2)/3 =**k**/2 - 2**k**+ 2 = 3/2***k**- 6 2 = 1/2***k**- 6 8 = 1/2***k****k**= 163 Answers · Science & Mathematics · 02/03/2009

**K**word ?? Got me I know the F word and the C word And the B words but the**K**word what Kitten ?6 Answers · Society & Culture · 19/10/2008

Goal: To get "

**k**" isolated by itself. a.) 0 = 14 +**k**In order to isolate... so that the 3.3 on the variable side will turn into 0 and will not count. -0.8 =**k**+ 3.3 -0.8 - 3.3 =**k**+ 3.3 - 3.3 -4.1 =**k**+ 0 Since the zero does...3 Answers · Science & Mathematics · 16/06/2011

**k**(x) = x² - 6**k**(x - 1) = (x - 1)² - 6**k**(x - 1) = x² - 2x + 1 - 6**k**(x...2(2x + 4) + 4 h(h(x)) = 4x + 8 + 4 h(h(x)) = 4x + 12 h(x) = 2x + 4,**k**(x) = x² - 6 h(**k**(x)) = 2(x² - 6) + 4 h(**k**(x)) = x²...2 Answers · Science & Mathematics · 21/09/2012

(

**k**- 2)x^2 + (**k**- 5)x - 5 = 0 The roots are equal if the discriminant... discriminant, b^2 - 4ac, evaluated as follows: (**k**- 5)^2 - 4(**k**- 2)(-5) And we want this to be equal to zero. (**k**...3 Answers · Science & Mathematics · 06/12/2008

In ecology,

**K**selection theory relates to the selection of combinations of ...to drive evolution in one of two generalized directions: r- or**K**-selection. These terms, r and**K**, are derived from...3 Answers · Science & Mathematics · 14/10/2009

**k**∫ (2kx - x^2)dx = 18 0 ....................**k**(kx^2 - x^3/3) | = 18 ....................0**k**(**k**^2) -**k**^3/3 - (**k**(0^2) - 0^3/3) = 18...1 Answers · Science & Mathematics · 02/05/2011

...e^(kx) - e^(-kx) ] / [ e^(3x) + e^(-3x) ] When x is large and assume

**k**>= 0 sinh(kx) / cosh(3x) ≈ e^(kx) / e^(3x) = e^(x(**k**- 3)) For sinh(kx...1 Answers · Science & Mathematics · 21/02/2019